Proceedings of the Eleventh ACM International Workshop on Data Engineering for Wireless and Mobile Access 2012
DOI: 10.1145/2258056.2258061
|View full text |Cite
|
Sign up to set email alerts
|

Alerting for vehicles demonstrating hazardous driving behavior

Abstract: Cooperative Collision Warning Systems (CCWSs) have become a major vehicle safety application in intelligent transportation systems. Vehicles organized in a vehicular ad-hoc network use a CCWS communication protocol to propagate emergency messages about hazardous events. Police cars, ambulances responding to incidents and speeding cars or motorcycles that constantly vary their speed, change lanes or commit other apparent traffic violations are examples of vehicles that demonstrate hazardous traffic patterns. Us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…A study by the National Highway Traffic Safety Administration (NHTSA) showed that V2V communication can reduce up to 80% of crashes [2]. Over the last decade, many researchers have proposed protocols and concepts to alert drivers of upcoming potential hazards by exchanging information with other vehicles using V2V communication [3], [4], [5], [6]. Based on information on the motion of neighboring vehicles, Sengupta et al presented the concept of a cooperative collision warning system that provides warnings and situation awareness displays to drivers [3].…”
Section: V2v Communicationmentioning
confidence: 99%
See 2 more Smart Citations
“…A study by the National Highway Traffic Safety Administration (NHTSA) showed that V2V communication can reduce up to 80% of crashes [2]. Over the last decade, many researchers have proposed protocols and concepts to alert drivers of upcoming potential hazards by exchanging information with other vehicles using V2V communication [3], [4], [5], [6]. Based on information on the motion of neighboring vehicles, Sengupta et al presented the concept of a cooperative collision warning system that provides warnings and situation awareness displays to drivers [3].…”
Section: V2v Communicationmentioning
confidence: 99%
“…Makanae et al proposed a prototype that utilizes a wireless local area network and a GPS to send messages to vehicles around a vehicle [17]. Verroios et al proposed a method for limiting the range of communication by utilizing a motion sensor and a GPS [4]. Moreover, techniques have been proposed to identify which vehicle communicates with one's vehicle by combining the vehicle position from V2V with the relative position and features from sensors such as an image sensor and a radar [18].…”
Section: V2v Communicationmentioning
confidence: 99%
See 1 more Smart Citation
“…While the authors of [4] use statistical measures, the authors of [14] combine a clustering algorithm with complex neuroscale and Bayesian factor analyses. A similar research is also performed in [16], where cars are analysed for potentially dangerous behaviour. However, the focus of the latter work lies more on the communication protocols between the traffic participants and not on their classification.…”
Section: Introductionmentioning
confidence: 99%